Butyric Acid Protects Against Renal Ischemia–Reperfusion Injury by Adjusting the Treg/Th17 Balance via HO-1/p-STAT3 Signaling - Chen, Zhen; Wang, Miaomiao; Yang, Shikun; Shi, Jian; Ji, Tianhao; Ding, Wei; Jiang, Lianghua; Fan, Zhiwen; Chen, Jing; Lu, Yunjie (Frontiers in Cell and Developmental Biology, 2021)
Immune regulation plays a vital role in ischemia–reperfusion injury (IRI). Butyric acid (BA) has immunomodulatory effects in many diseases, but its immunomodulatory effects during renal IRI are still unclear. Our research shows that BA protected against IRI and significantly improved renal IRI in vivo. In vitro studies showed that BA inhibits Th17 cell differentiation and induces Treg cell differentiation. Mechanism studies have shown that heme oxygenase 1 (HO-1)/STAT3 signaling pathway was involved in the inhibitory effect of BA on Th17 cell differentiation. HO-1 inhibitors can significantly rescue the BA-mediated inhibition of Th17 cell differentiation. We confirmed that BA promotes the differentiation of Th17 cells into Treg cells by regulating the pathway and reduces renal IRI.